Features of organization of virtual enterprise еngineering and technical service of automobile transport ”HNADU TESA” - Volkov, V. P.; Komov, P. B.; Komov, O. B.; Hrytsuk, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The peculiaritiesand results ofthe organization ofvirtual enterpriseengineering andtechnical service of automobile transport«HNADU TESA» are considered in the paper. The variant of transition of structure of virtual enterprise is presented from automated functioning in the automatic mode.